Altered Phase Separation and Cellular Impact in C9orf72-Linked ALS/FTD - Solomon, Daniel A.; Smikle, Rebekah; Reid, Matthew J.; Mizielinska, Sarah (Frontiers in Cellular Neuroscience, 2021)
Since the discovery of the C9orf72 repeat expansion mutation as causative for chromosome 9-linked amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) in 2011 a multitude of cellular pathways have been implicated. However, evidence has also been accumulating for a key mechanism of cellular compartmentalisation – phase separation. Liquid-liquid phase separation (LLPS) is fundamental for the formation of membranelles organelles including stress granules, the nucleolus, Cajal bodies, nuclear speckles and the central channel of the nuclear pore. Evidence has now accumulated showing that the formation and function of these membraneless organelles is impaired by both the toxic arginine rich DPRs, , translated from the C9orf72 repeat RNA transcript, and the repeat RNA itself. Both the arginine rich DPRs and repeat RNA themselves undergo phase separation and disrupt the physiological phase separation of proteins involved in the formation of these liquid-like organelles. Hence abnormal phase separation may explain a number of pathological cellular phenomena associated with C9orf72-ALS/FTD. In this review we will discuss the principles of phase separation, phase separation of the DPRs and repeat RNA themselves and how they perturb LLPS associated with membraneless organelles and the functional consequences of this. We will then discuss how phase separation may impact the major pathological feature of C9orf72-ALS/FTD, TDP-43 proteinopathy and how LLPS may be targeted therapeutically in disease.